Bentuk Lingual dalam Meme pada Grup Whatsapp - Rachmawati, Dian; Imbang, Djeinnie; Kalangi, Leika Maria Victoria (Universitas Sam Ratulangi, 2019)
This study examines the lingual forms especially the morphological process and the lingual form of sentences based on the communicative values contained in the meme of the whatsapp group. The things discussed will reveal the lingual forms of words and sentences in meme on whatsapp group. This study aims to identify, classify, and analyze the lingual forms in meme on whatsapp group. This research is descriptive qualitative with a linguistic approach. The method of data collection uses the referred method. The method of data analysis uses a matching method with basic and advanced techniques. The results of the study show that there are six lingual forms of words according to the morphological processes in the meme of the whatsapp group, which consist of zero derivation, affixation (prefix, suffix, confix, and combination of affixes), reduplication (dwilingga and dwiwasana), abbreviation (decapitation, abbreviation, contractions, and acronyms), composition, and reverse derivation. The result of the study of the lingual sentence shows that there are four types of sentences, namely declarative sentences, interrogative sentences (total and partial interrogatives), imperative sentences (common imperatives, requests, invitation, and imperative), and empathic sentences in meme on whatsapp group.Keywords: shapes, lingual, words, sentences, memes